1985
DOI: 10.1126/science.230.4726.625
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Tillage

Abstract: Conservation production systems combine tillage and planting practices to reduce soil erosion and loss of water from farmland. Successful conservation tillage practices depend on the ability of farm managers to integrate sound crop production practices with effective pest management systems. More scientific information is needed to determine the relations between tillage practices and physical, chemical, and biological soil factors that affect plant and pest ecology. There is a need to devise improved pest man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
0
1

Year Published

1987
1987
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(103 citation statements)
references
References 18 publications
1
101
0
1
Order By: Relevance
“…The main objective of conservation tillage is to reduce runoff and soil erosion (Gebhardt et al, 1985).…”
Section: Runoffmentioning
confidence: 99%
“…The main objective of conservation tillage is to reduce runoff and soil erosion (Gebhardt et al, 1985).…”
Section: Runoffmentioning
confidence: 99%
“…Generally, under tillage systems that include ploughing, which are conventional in Europe, the hydraulic conductivity (K) increases on tillage events and then decreases during the growing season due to the settling of the soil structure created by tillage (Angulo-Jaramillo et al, 1997;Azevedo et al, 1998;Bormann and Klaassen, 2008). Coquet et al (2005) showed that tillage, especially ploughing, creates macroporosity that temporarily increases saturated and near-saturated K. Under conservation practices, defined as those practices that keep at least 30% of the soil surface covered with residues (Gebhardt et al, 1985), soil disturbance by tillage is minimized but the structure of the surface soil is affected by the presence of organic residues which can enhance infiltration rates (Findeling et al, 2003). Crop residues absorb rainfall energy and prevent soil surface from crusting or sealing (Blevins and Frye, 1993;Baumhardt and Lascano, 1996), the splash effect of rain is reduced and aggregate stability is generally improved (Mamedov et al, 2000;Six et al, 2000;Baumhardt et al, 2004;Pinheiro et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Deep tillage of the soil, as is done with conventional methods, removes 2::70% of all vegetative residue from the ground surface, and consequently disrupts the life cycles of many species. Conservation tillage practices leave 2::30% plant residue on the soil surface after planting (Gebhardt et al 1985). One conservation practice is no tillage, which leaves 2::60% of plant residue on the soil surface after planting.…”
Section: The Us Government Established the Conservationmentioning
confidence: 99%